Learning Outcomes on the Importance of Ethics in TikTok Social Media - Nasution, Lannuria (Progressive of Cognitive and Ability, 2025)
In the era of digital and globalization, social media platforms have become an important part of daily life throughout society, especially among teenagers. One platform that is growing in popularity is TikTok, a short video sharing application that allows users to create, edit and share their creative content with an audience. However, the rapid growth of TikTok also raises concerns about its impact on teenage ethics. The method used is literature study, a technique carried out by collecting data from various sources, such as books, journals, etc. This research examines the ethics of using social media, especially the TikTok platform, through a literature study. TikTok, as one of the most popular video sharing applications, has a significant impact on user behavior and digital culture. This research identifies various ethical aspects, including privacy, dissemination of correct information, and the influence of content on teenagers. The analysis was carried out by referring to various literature that discusses ethical challenges in social media, such as privacy violations and the negative impact of harmful content. The findings suggest that users and content creators need to increase awareness of their ethical responsibilities to create a safer and more positive digital environment. Recommendations are aimed at developing ethical guidelines that are acceptable to TikTok users and other stakeholders.